PELATIHAN ADMINISTRASI DALAM BERWIRAUSAHA UNTUK USAHA MIKRO DAN MAKRO MASYARAKAT KAPLING SUKASARI TANGERANG - Luky Thio (Jurnal Abdi Mandala, 2023)
Nowadays there are many Small and Medium Enterprises (SMEs) that are unable to maintain business continuity so it is not uncommon for bankruptcy to occur in less than five years. Most entrepreneurs don't know what mistakes make their small businesses go bankrupt. Even though Indonesia's economic growth is getting better, one of the causes of the lack of success of SMEs is the administration of these SMEs. Poor administration makes SMEs complacent and not paying attention to the condition of their SMEs. The target audience for this PKM activity is UKM Sukasari Tangerang. Training is carried out using lecture methods, demonstrations and exercises accompanied by questions and answers. The demonstration method is used to show a work process, namely the administrative stages of entrepreneurship in making reports. Meanwhile, the question and answer method provides participants with the opportunity to consult in overcoming obstacles in entrepreneurship, especially in administration. The benefits that participants can get from this PKM activity include being able tocarry out general administrative activities to make financial reports and tax reporting in entrepreneurship.